ANALISIS SWOT DALAM MENENTUKAN STRATEGI PENJUALAN DI TOKO SEJAHTERA SANGATTA - Anisa Ayu Lestari; Amirudin; Indra Wahyudi (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2020)
The purpose of this study was to determine the existing sales strategy at Toko Sejahtera based on a SWOT analysis. The population observed was the head of the Sangatta Sejahtera Store, admin, cashier, waiter, and driver. Data collection techniques in this study were interviews and the distribution of open-ended questionnaires and answers given from the shop and employees. The analytical tools used are EFAS, IFAS, SWOT matrix, IE Matrix and QSPM strategy. The results of the research from the analysis stage carried out are obtained sales strategies that must be further improved market penetration strategies and product development strategies. Based on the results of the EFAS and IFAS matrix analysis as well as the matching of the SWOT and IE analysis, the QSPM results have a market penetration TAS value of 5.60 and a product development TAS of 5.50. This should be paid more attention in order to increase sales at the store